Instrumenty procesowe przeciwdziałające nadużyciu prawa do żądania wyłączenia sędziego - Bińczyk, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
The institution of disqualiﬁcation of judge is an important guarantee for the constitutional right to impartial court. However, when it is used for purposes contrary to its ratio legis, it harms the authority and good reputation of a judicial system. Instruments which can be used in the administrative court procedure to counteract abuse of the right of a party to motion disqualiﬁcation of judge have been provided for in the Act of 30 August 2002 on the Proceedings before Administrative Courts. They may also derive from judicial decisions. These instruments have been analysed with a view of establishing whether they are sufficient to prevent abuse of such right effectively. First, however, the institution of disqualiﬁcation of judge has been outlined. The Act of 9 April 2015 amending the Act on Proceedings before Administrative Courts introduced substantial amendments to the procedural instruments which been discussed separately as the instruments from before and after the date of their enforcement i.e. 5 August 2015. As the analysis showed, administrative courts have not elaborated uniform mechanisms of action in relation to a motion for disqualiﬁcation of judge. Consequently, not all actions help to speed up the proceeding. Moreover, a ﬁne for submitting a motion in bad faith available to an administrative court to apply to the entity submitting a motion in bad faith has been eliminated too hastily. On the other hand, the new regulations concerning a motion for disqualiﬁcation of court and resubmittal of the motion for disqualiﬁcation of judge have been assessed positively.
Procedural instruments counteracting abuse of the right to motion disqualiﬁ cation of judge
Keywords: right to impartial court; abuse of the right; disqualiﬁ cation of judge; administrative court; court and administrative procedure